Temporal muscle thickness and survival in patients with amyotrophic lateral sclerosis. (2nd November 2022) - Vinciguerra, Claudia; Toriello, Antonella; Nardone, Valerio; Romano, Daniele; Tartaglione, Salvatore; Abate, Filomena; Landolfi, Annamaria; Barone, Paolo
ABSTRACT: Temporal muscle thickness (TMT) is a new potential MRI biomarker, which has shown prognostic relevance in neuro-oncology. We aim at investigating the potential prognostic value of TMT in patients with Amyotrophic Lateral Sclerosis (ALS). We retrospectively evaluated 30 ALS patients, whose clinical, Magnetic Resonance Imaging (MRI) and Electrodiagnostic testing (EDX) data were available, in comparison to age-matched 30 healthy subjects. TMT calculated on T1-weighted MR images was significantly lower in ALS patients than in healthy subjects (p < 0.001), correlating with the ALS Functional Rating Scale (FRS) (p:0.018) and compound motor action potential (CMAP) (p:0.012) in the patients group. Multivariate analysis of overall survival (OS) showed that the only parameters that remained significant were TMT (p:0.002, OR 0.45, 95%vCI: 0.28–0.75) and ALS FRS-R (p:0.023, OR: 0.80, 95%CI: 0.67–0.92). TMT seems to be a promising surrogate biomarker of survival and functional status in ALS. Our data deserve further investigations in multicenter and prospective trials.